Fibrinogen Level Deteriorates before Other Routine Coagulation Parameters and Massive Transfusion in the Early Phase of Severe Trauma: A Retrospective Observational Study - Hayakawa, Mineji; Gando, Satoshi; Ono, Yuichi; Wada, Takeshi; Yanagida, Yuichiro; Sawamura, Atsushi (Seminars in Thrombosis and Hemostasis, 2015)
In trauma, hemostatic functions should be maintained appropriately to prevent massive bleeding. This study elucidated the time-dependent changes in platelet count and coagulation variables, and the effects of disseminated intravascular coagulation (DIC) on these changes during the early phase of trauma. Trauma patients with an injury severity score ≥16 were enrolled. The critical levels of platelet count and coagulation variables were defined according to recent trauma guidelines. Massive transfusion was defined as >10 units red cell concentrate. The time from arrival at the emergency department to reaching the critical levels and meeting the criteria for massive transfusion were evaluated. Eighty trauma patients were enrolled; 35 were diagnosed with DIC on arrival. Among all patients, fibrinogen levels reached the critical level earliest among routine coagulation parameters; other routine coagulation parameters deteriorated after the patients met the criteria for massive transfusion. Routine coagulation parameters reached their critical levels earlier in DIC patients than patients without DIC. Massive transfusion was performed more frequently in DIC patients, who met the criteria earlier. During the early phase of trauma, fibrinogen levels deteriorate earlier than other routine coagulation parameters, especially in DIC patients.
Keywords: disseminated intravascular coagulation; fibrinolysis; fibrinogenolysis; coagulopathy; bleeding